Human Resource Management Strategy, Work Environment, Organizational Culture, and Employee Work Motivation: Evidence from PT Perkebunan Nusantara 1 Regional 7, Lampung Province - Vajri Fharma Putra; Sofyan Mubarok; Ferry Hermanto; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
This study examines the effects of human resource management (HRM) strategy and the work environment on employee work motivation, with organizational culture positioned as an intervening variable, in PT Perkebunan Nusantara 1 Regional 7, Lampung Province. Design/methodology/approach: An explanatory quantitative survey design was employed. Data were collected from 82 employees using a structured questionnaire with five-point Likert-type responses. The conceptual model was tested using partial least squares structural equation modeling (PLS-SEM) with SmartPLS. Findings: The work environment had a positive and significant effect on organizational culture (β = 0.507, t = 3.534, p < 0.001) and employee work motivation (β = 0.545, t = 3.695, p < 0.001). In contrast, HRM strategy did not significantly affect organizational culture (β = 0.124, t = 0.795, p = 0.427) or work motivation (β = 0.026, t = 0.201, p = 0.841). Organizational culture also did not significantly affect work motivation (β = 0.131, t = 0.850, p = 0.396). The model explained 36.4% of the variance in organizational culture and 42.4% of the variance in work motivation. Originality/value: The findings indicate that the immediate work environment is a more salient driver of employee motivation than formal HRM strategy in the studied organizational context. The study contributes to HRM and organizational behavior literature by showing that organizational culture does not automatically translate HRM strategy or workplace conditions into motivation unless employees experience the culture as behaviorally meaningful in daily work.